What improvements do general exercise training and traditional Chinese exercises have on knee osteoarthritis? A narrative review based on biological mechanisms and clinical efficacy - Du, Xingbin; Fan, Rao; Kong, Jianda (Frontiers in Medicine, 2024)
Background Knee osteoarthritis (KOA) is a disease that significantly affects the quality of life of patients, with a complex pathophysiology that includes degeneration of cartilage and subchondral bone, synovitis, and associations with mechanical load, inflammation, metabolic factors, hormonal changes, and aging. Objective This article aims to comprehensively review the biological mechanisms and clinical effects of general exercise training and traditional Chinese exercises (such as Tai Chi and Qigong) on the treatment of KOA, providing references for the development of clinical exercise prescriptions. Methods A systematic search of databases including PubMed, Web of Science, Google Scholar, and China National Knowledge Infrastructure (CNKI) was conducted, reviewing studies including randomized controlled trials (RCTs), observational studies, systematic reviews, and meta-analyses. Keywords included “knee osteoarthritis,” “exercise therapy,” “physical activity,” and “traditional Chinese exercise.” Results and conclusion General exercise training positively affects KOA by mechanisms such as promoting blood circulation, improving the metabolism of inflammatory factors, enhancing the expression of anti-inflammatory cytokines, and reducing cartilage cell aging. Traditional Chinese exercises, like Tai Chi and Qigong, benefit the improvement of KOA symptoms and tissue repair by regulating immune function and alleviating joint inflammation. Clinical studies have shown that both types of exercise can improve physical function, quality of life, and pain relief in patients with KOA. Both general exercise training and traditional Chinese exercises are non-pharmacological treatment options for KOA that can effectively improve patients’ physiological function and quality of life. Future research should further explore the long-term effects and biological mechanisms of these exercise interventions and develop personalized exercise programs based on the specific needs of patients.